Analysis of Increasing The Competitiveness of MSME Business through Entrepreneurial Competence, Entrepreneurial Orientation, and Customers Relationship Management - Sembiring, Lenny Dermawan; Setyawati, Amelia; Indajang, Kevin; Doloksaribu, Winda Sri Astuti; Sudirman, Acai (President University, 2023)
MSME actors are starting to be concerned about management governance and trying to improve their abilities by participating in several competency-based training held by the central government and regional governments. Even so, only some MSMEs can develop their business competitiveness. This study mainly aims to analyze the increase in the competitiveness of MSME businesses through entrepreneurial competence, entrepreneurial orientation, and customer relationship management. This study used a library and field research design with a causal associative approach. This study used a total sample of 170 samples. Data analysis confirms that entrepreneurial competence, orientation, and customer relationship management significantly affect MSME Competitiveness. The implications of this research highlight the importance of developing entrepreneurial competencies for SMEs. The implication is that MSMEs must invest time and resources in training and developing entrepreneurial skills to increase brand competitiveness. Furthermore, the importance of customer relationship management (CRM) in increasing the competitiveness of MSMEs. Furthermore, MSMEs need to pay attention to relationship management with their customers. They must understand customer needs, provide quality service, and build long-term customer relationships.